Anti-CD80/86 antibodies inhibit inflammatory reaction and improve graft survival in a high-risk murine corneal transplantation rejection model - Jun Zhu; Takenori Inomata; Masahiro Nakamura; Keiichi Fujimoto; Yasutsugu Akasaki; Kenta Fujio; Ai Yanagawa; Koichiro Uchida; Jaemyoung Sung; Naoko Negishi; Ken Nagino; Yuichi Okumura; et al. (Scientific Reports, 2022)
Abstract We investigated the effects of anti-CD80/86 antibodies in a murine high-risk corneal transplantation rejection model. A mixed lymphocyte reaction (MLR) assay was conducted with anti-CD80/86 antibodies. Inflammatory cytokine levels in the culture supernatant were measured using an enzyme-linked immunosorbent assay. Interferon (IFN)-γ-producing CD4+ T cell frequencies in the MLR were assessed using flow cytometry. In vivo, high-risk corneal allograft survival and IFN-γ-producing CD4+ T cell frequencies in corneal grafts were assessed with intraperitoneal injection of anti-CD80/86 antibodies compared to phosphate-buffered saline (PBS). RNA-sequencing was performed on corneal grafts 2 weeks post-transplantation. Anti-CD80/86 antibodies significantly decreased T-cell proliferation, IFN-γ+-producing CD4+ T cell frequencies, and IFN-γ, interleukin (IL)-1β, IL-2, IL-10, and tumor necrosis factor-α production in the MLR compared to PBS injection. Intraperitoneal injection of anti-CD80/86 antibodies significantly prolonged corneal graft survival and decreased IFN-γ+-producing CD4+ T cell frequencies compared to PBS injection. Gene set enrichment analysis showed that the gene sets mainly enriched in the control group were related to allograft rejection and inflammatory response compared to PBS injection. Anti-CD80/86 antibodies significantly prolonged corneal graft survival by inhibiting T-cell proliferation and inflammatory response.